Women’s Agency and Gender Negotiation in Jonggan Dance: Cultural Preservation in the Era of Modernization and Creative Industries - Mega Cantik Putri Aditya; Aline Rizky Oktaviari Satrianingsih; Mukhamad Zulianto; Amanda Ristriana Pattisinai (Jurnal Mamangan, 2026)
The Jonggan performing art, as a cultural heritage of the Dayak Kanayatn community, faces preservation challenges amid shifting gender values and contemporary cultural dynamics, particularly regarding the position and role of women in performance practices. This study aims to analyze the role of women in Jonggan performance as a process of gender value transformation and its implications for the preservation of traditional Dayak Kanayatn performing arts. The analysis is grounded in gender theory and cultural performativity, which conceptualize the body, social roles, and artistic practices as spaces for symbolic meaning articulation and value negotiation. This research employs a qualitative approach using a new ethnographic framework through participant observation, in-depth interviews, and visual documentation analysis of Jonggan performances conducted in customary rituals and cultural festivals. The informants consisted of ten individuals selected through purposive sampling, with the criteria including community members who had experience in the implementation of local wisdom, as well as community leaders who actively promote and regularly carry out traditional practices and local wisdom. The findings reveal that women’s involvement in Jonggan is not merely visual or aesthetic but represents symbols of fertility, hospitality, and social cohesion rooted in Dayak Kanayatn cosmology, while simultaneously functioning as mediators of gender value transformation in sustaining traditional arts. The novelty of this research lies in its interpretation of women’s roles not only as performers but also as agents of cultural transformation and empowerment within a tradition-based creative economy.